1993
DOI: 10.1002/ddr.430300308
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol‐induced reinforcement: Dopamine and 5‐HT3 receptor interactions in animals and humans

Abstract: Alcohol abuse i s a major health problem worldwide. Whatever the treatment goal, be it abstinence or "controlled" drinking, the outcome from both pharmacological and nonbiological treatments remains disappointing. Behavioural experiments in animals have suggested that the reinforcing properties of alcohol, like other drugs of abuse, are critical to drug-seeking behaviour. Dopaminergic fibres running from the ventral tegmental area to the nucleus accumbens may play a central role in mediating the reinforcing ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 118 publications
0
13
0
Order By: Relevance
“…Behavioral pharmacological studies show that many of alcohol's rewarding effects are mediated by interactions between DA and 5-HT 3 receptors in the midbrain and cortex (Wise and Bozarth 1987;Koob 1992;Johnson and Cowen 1993;Barnes and Sharp 1999;Hemby et al 1997b). 5-HT 3 receptors are densely distributed in the terminals of mesocorticolimbic DA-containing neurons where they regulate DA release in these brain regions (Kilpatrick et al 1987(Kilpatrick et al , 1996Oxford et al 1992).…”
Section: -Ht 3 Antagonistsmentioning
confidence: 95%
See 2 more Smart Citations
“…Behavioral pharmacological studies show that many of alcohol's rewarding effects are mediated by interactions between DA and 5-HT 3 receptors in the midbrain and cortex (Wise and Bozarth 1987;Koob 1992;Johnson and Cowen 1993;Barnes and Sharp 1999;Hemby et al 1997b). 5-HT 3 receptors are densely distributed in the terminals of mesocorticolimbic DA-containing neurons where they regulate DA release in these brain regions (Kilpatrick et al 1987(Kilpatrick et al , 1996Oxford et al 1992).…”
Section: -Ht 3 Antagonistsmentioning
confidence: 95%
“…Demonstration that 5-HT 3 receptor blockade reduces DA activity, and therefore the rewarding effects of abused drugs (including alcohol) comes from at least three different animal paradigms. 5-HT 3 receptor antagonists: a) attenuate hyperlocomotion in the rat induced by DA or ethanol injection into the nucleus accumbens (Bradbury et al 1985); b) inhibit DiMe-C7 (a neurokinin) induced hyperlocomotion which is also attenuated by the DA antagonist, fluphenazine (Eison et al 1982;Hagan et al 1990), and c) 5-HT 3 receptor antagonists decrease alcohol consumption in several animal models and across different species (Costall et al 1987;Fadda et al 1991;Sellers et al 1992;Hodge et al 1993;Johnson et al 1993;Meert 1993;Dyr and Kostowski 1995;Tomkins et al 1995;McBride and Li 1998;Rodd-Henricks et al 1999;Barnes and Sharp 1999;cf. Beardsley et al 1994).…”
Section: -Ht 3 Antagonistsmentioning
confidence: 97%
See 1 more Smart Citation
“…Pharmacobehavioral studies show that many of alcohol's reinforcing effects are mediated by 5-HT 3 and dopamine interactions in the cortico-mesolimbic system [9,[213][214][215][216].…”
Section: Serotonin-3 (5-ht 3 ) Receptor Antagonistsmentioning
confidence: 99%
“…In two distinct experiments, Johnson and Cowen [214] and Johnson et al [224] showed that ondansetron pretreatment attenuated lowdose alcohol-induced positive subjective effects (including the desire to drink). Swift et al [230], using much higher alcohol and ondansetron doses, also discovered that ondansetron compared with placebo pretreatment reduced alcohol preference; however, a mixture of both stimulant and sedative interactions between ondansetron and alcohol also was observed.…”
Section: Serotonin-3 (5-ht 3 ) Receptor Antagonistsmentioning
confidence: 99%